Pengaruh Cahaya dan NaHCO3 terhadap Laju Reaksi Fotosintesis pada Hydrilla verticilata - Nasution, Marina Azzahra; Ruth Susanty, Revi; Limbong, Forentina; Harahap, Fauziyah; Silitonga, Melva; Edi, Syahmi (Universitas Islam Jember, 2025)
Photosynthesis is an important process for plants to produce energy through the conversion of carbon dioxide and water into glucose and oxygen with the help of light energy. Environmental factors such as light intensity, carbon dioxide availability, temperature, and water concentration affect the rate of photosynthesis. This study aims to analyze the effect of light and NaHCO₃ (Sodium Bicarbonate) concentration on the speed of photosynthesis process in plants. One way to increase the availability of carbon dioxide for plants is by adding NaHCO₃ (Sodium Bicarbonate) solution. In this experiment, variations in light intensity, irradiation time and NaHCO₃ concentration were used to observe the rate of photosynthesis as measured by changes in the amount of oxygen produced. The results of this study indicate that both light and NaHCO₃ have an important role in influencing the rate of photosynthesis, but there is an optimal limit where further increase does not give significant results.